The Beginnings of Western Science. - Lindberg, David C.. (Chicago The University og Chicago Press, 1992)
This is the first attempt in two decades to surwey the science of the ancient world, the first attempt in four decades to write a comprehensive history of medieval science, and the first attempt ever to present a full, unified account of both ancient and medieval science in a single volume.
Keywords: History